2021
DOI: 10.3390/biology10080808
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD3+, CD8+, or FoxP3+ T Lymphocyte Infiltrations Are Associated with the Pathogenesis of Colorectal Cancer but Not with the Overall Survival of Patients

Abstract: Tumor-infiltrating lymphocytes include heterogeneous populations of T lymphocytes that play crucial roles in the tumor immune response; importantly, their presence in the tumor tissue may predict clinical outcomes. Therefore, we herein studied the prognostic significance of the presence and location of CD3+, CD8+, and FoxP3+ T lymphocytes in colorectal cancer samples. In the intratumor analysis, our data did not reveal any association between lymphocyte infiltrations with clinical or pathological data. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
7
0
1
Order By: Relevance
“…This phenomenon is not consistent with the majority of other results [26,27]. However, a number of studies also failed to show the expected correlation-entirely or, at least, in some of the analyzed cohorts [28][29][30][31]. It is speculated that the lack of correlation between density of TILs and survival or other prognostic factors (e.g., stage of disease) may be due to environmental variables, such as the microbiome or tumor inflammatory status [32,33].…”
Section: Discussionmentioning
confidence: 65%
“…This phenomenon is not consistent with the majority of other results [26,27]. However, a number of studies also failed to show the expected correlation-entirely or, at least, in some of the analyzed cohorts [28][29][30][31]. It is speculated that the lack of correlation between density of TILs and survival or other prognostic factors (e.g., stage of disease) may be due to environmental variables, such as the microbiome or tumor inflammatory status [32,33].…”
Section: Discussionmentioning
confidence: 65%
“…Accordingly, in the present study, we assessed the CD3 and CD8 expressions in the IM and CT to evaluate their prognostic potential in CRC, however similar to Barbosa et al. ( 42 ), no statistically significant association was found in the total cohort. Since proximal and distal CRC displays distinct epidemiological, pathological, and clinical entities ( 2 , 3 ), we further analyzed TILs infiltration and their association with clinical outcomes based on the tumor location.…”
Section: Discussionmentioning
confidence: 65%
“…Similar observations were made by other authors who showed that high densities of tumor-infiltrating CD8 + cells are associated with improved disease-free and overall survival in CRC, and the high immune cell infiltration by cytotoxic CD8 + T-cells has a favorable prognostic significance 35 . Additionally, it was shown that the presence of high infiltrations of CD3 +, CD8 + lymphocytes in the tumor margins was associated with TNM stages I-II and the absence of lymph node metastases 36 .…”
Section: Discussionmentioning
confidence: 99%